Chronic viral hepatitis D - the current state of a problem. - Aliya Konysbekova (National Scientific Medical Center, 2017)
Chronic hepatitis D- severe and rapidly progressing form of viral hepatitis, leading to the liver cirrhosis in 70% of cases within 5-10 years. HDV RNA replicates only in the presence of viral hepatitis B. Introduction to the calendar of immunization vaccination in the Republic of Kazakhstan led to a reduction in the incidence of hepatitis B is almost 40 times. However, despite the ongoing eﬀective measures, the amount of detectable virus mixed in with the delta agent is increased and is now at a global map of Kazakhstan refers to medium-endemic countries. Against the background of rapid progress in the treatment of hepatitis C, hepatitis B treatment of existing schemes in the delta agent ineﬀective, allowing HDV considered as one of the most virulent and dangerous hepatotropic virus.